Potentiodynamic behaviour of graphite and platinum electrodes in sodium nitrite-potassium nitrite melts - Sustersic, M. G. (1974)
The potentiodynamic behaviour of graphite and platinum electrodes was studied in alkaline nitrite melts. No appreciable corrosion of graphite was observed, due to the apparently low concentration of highly oxidising species. Rate processes such as NO2 ion oxidation. NO2 reduction and OH- ion oxidation were studied and interpreted with formerly discussed reaction pathways.